2020
DOI: 10.5021/ad.2020.32.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Timing of Surgical Excision in Pediatric Pilomatricoma: Association between Clinicopathological Features and Cosmetic Outcomes

Abstract: Background: The treatment of choice for pilomatricomas is surgical excision; however, data for the optimal timing of treatment and cosmetic outcomes are limited. Objective: This study aimed to investigate the optimal timing of treatment in pilomatricomas by considering clinicopathological findings and cosmetic outcomes. Methods: Seventy-three pilomatricomas patients aged ≤15 years were retrospectively reviewed. Patients were classified into early excision (disease duration ≤12 months, group A) and delayed exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…19 Another human study described 44 pilomatricomas, and reported a significative blood flow with colour Doppler ultrasonography in 22 cases, without any difference from other subcutaneous tumours. 22 Doppler signal detection in pilomatricoma was also noted by other authors [24][25][26][27] ; however, it seems that the presence of a blood flow within the soft tissue content of the mass could be consistent with a pilomatricoma, but absence of this feature cannot rule out this entity. The presence of several blood vessels on histology correlates with ultrasound findings, and the pathogenesis of this hypervascularisation is still unknown.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…19 Another human study described 44 pilomatricomas, and reported a significative blood flow with colour Doppler ultrasonography in 22 cases, without any difference from other subcutaneous tumours. 22 Doppler signal detection in pilomatricoma was also noted by other authors [24][25][26][27] ; however, it seems that the presence of a blood flow within the soft tissue content of the mass could be consistent with a pilomatricoma, but absence of this feature cannot rule out this entity. The presence of several blood vessels on histology correlates with ultrasound findings, and the pathogenesis of this hypervascularisation is still unknown.…”
Section: Discussionsupporting
confidence: 58%
“…In our case, a moderate blood flow at the periphery and inside the mass was detected, without any distinct pattern. The presence of a fluid component, reported in several human studies, 17,21,24,27 reflects cystic degeneration and could be caused by the inflammatory response to the release of keratinised debris, mimicking the presence of a foreign body. In our case, a cystic fluid component was also noted as well as a hypoechoic peripheral rim.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations